Valoración del riesgo de caries dental : una herramienta para la atención integral del niño (2006)
ABSTRACT: This article explores the state of the art about caries risk assessment, and its importance in a contemporary preventive approach based on new concepts about the caries process. After a review of the factors proposed for the determination of individual caries risk and the progression of dental caries, an analysis about the possibilities of risk assessment and its contribution towards a comprehensive dental care for the pediatric patient is offered.